APPLYING KOTTER'S 8 STEP MODEL OF CHANGE IN THE DISPLACED UNIVERSITY'S MANAGEMENT - NESTORENKO, Tetyana; KRAVCHYK, Yurii; NESTORENKO, Oleksandr; KOINASH, Maryna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article explores the strategic relocation of Ukrainian universities during the ongoing war with Russia, focusing on Berdyansk State Pedagogical University (BSPU) as a case study. Historically rooted in the Azov region since 1932, BSPU was compelled to relocate to Zaporizhzhia in April 2022 due to the full-scale Russian invasion. The study examines the multifaceted challenges universities face in conflict zones, emphasizing the necessity of robust strategic planning and adaptive management tools. Among these, scenario planning is identified as a critical methodology for ensuring organizational resilience, enabling universities to anticipate diverse futures, manage uncertainty, and maintain operational continuity. The research adopts a qualitative case study methodology to assess BSPU’s relocation, revealing that wartime relocation affects not only the physical movement of institutions but also has profound psychological, organizational, and academic implications. A key focus is the importance of scenario planning as a decision-making tool that facilitates proactive thinking, flexible strategies, and institutional preparedness. The article discusses how scenario planning – widely used in business and military sectors – can be successfully adapted to higher education, particularly in situations of displacement, crisis, and uncertainty. The case of BSPU highlights critical components for successful adaptation: maintaining human capital, transitioning to digital learning environments, developing strategic partnerships, implementing financial resilience strategies, and ensuring academic competitiveness. The research also incorporates a modified version of Kotter’s 8-Step Change Management Model, enhanced with a new step – Resource Assessment and Support – to reflect the unique needs of universities during wartime. This adapted model provides a structured framework for managing large-scale organizational change under crisis conditions. The study argues that Ukrainian universities must become not only survivors of the current conflict but also strategic actors in post-war national reconstruction. By aligning academic programs with societal needs and strengthening internal and external support networks, displaced universities can reposition themselves as innovative, forward-thinking institutions. The BSPU case illustrates how comprehensive planning, flexible leadership, and community engagement are essential for academic continuity and long-term sustainability in times of profound uncertainty.
Keywords: changes; war; relocated university; management; Kotter's model